Signaling Strategies of Malaria Parasite for Its Survival, Proliferation, and Infection during Erythrocytic Stage - Soni, Rani; Sharma, Drista; Rai, Praveen; Sharma, Bhaskar; Bhatt, Tarun K. (Frontiers in Immunology, 2017)
Irrespective of various efforts, malaria persist the most debilitating effect in terms of morbidity and mortality. Moreover, the existing drugs are also vulnerable to the emergence of drug resistance. In order to explore the potential targets for designing the most effective anti-malarial therapies, it is required to focus on the facts of biochemical mechanism underlying the process of parasite survival and disease pathogenesis. This review is intended to bring out the existing knowledge about the functions and components of the major signaling pathways such as kinase signaling, calcium signaling, cyclic nucleotide based signaling, serving the various aspects of the parasitic asexual stage and highlighted the Toll like receptors (TLR), GPI (Glycosylphosphatidylinositol) mediated signaling and molecular events in cyto-adhesion which elicit the host immune response. This discussion will facilitate a look over essential components for parasite survival and disease progression to be implemented in discovery of novel anti-malarial drugs and vaccines.